Internal Zn allocation influences Zn deficiency tolerance and grain Zn loading in rice (Oryza sativa L.) - Somayanda, Impa M.; Gramlich, Anja; Tandy, Susan; Schulin, Rainer; Frossard, Emmanuel; Beebout, Sarah E. (Frontiers in Plant Science, 2013)
One of the important factors that influences Zn deficiency tolerance and grain Zn loading in crops is the within-plant allocation of Zn. Three independent experiments were carried out to understand the internal Zn distribution patterns in rice genotypes grown in Zn-sufficient and Zn-deficient agar nutrient solution (ANS). In one of the experiments, two rice genotypes (IR55179 and KP) contrasting in Zn deficiency tolerance were leaf-labeled with 65Zn. In the other two experiments, two Zn biofortification breeding lines (IR69428 and SWHOO) were either root- or leaf-labeled with 65Zn. Rice genotype IR55179 showed significantly higher Zn deficiency tolerance than KP at 21 and 42 days after planting. When KP was Zn-deficient, it failed to translocate 65Zn from the labeled leaf to newly emerging leaves. Similarly, the root-to-shoot translocation of unlabeled Zn was lower in KP than in IR55179. These results suggest that some Zn-efficient rice genotypes have greater ability to translocate Zn from older to actively growing tissues than genotypes sensitive to Zn deficiency. Among the two Zn biofortication breeding lines that were leaf-labeled with 65Zn at 10 days before panicle initiation stage, 65Zn distribution in the grains at maturity was similar between both genotypes in Zn-sufficient conditions. However, under Zn-deficient conditions, SWHOO accumulated significantly higher 65Zn in grains than IR69428, indicating that SWHOO is a better remobilizer than IR69428. When the roots of these two Zn biofortication breeding lines were exposed to 65Zn solution at 10 days after flowering, IR69428 showed higher root uptake of 65Zn than SWHOO in Zn-sufficient conditions, but 65Zn allocation in the aerial parts of the plant was similar between both genotypes.